A Rapid Gamma‐Ray Glow Flux Reduction Observed From 20 km Altitude. Issue 9 (6th May 2021) - Kochkin, P.; Sarria, D.; Lehtinen, N.; Mezentsev, A.; Yang, S.; Genov, G.; Ullaland, K.; Marisaldi, M.; Østgaard, N.; Christian, H. J.; Grove, J. E.; Quick, M.; et al.
Abstract: Two gamma‐ray glows were observed by a high‐altitude NASA ER‐2 aircraft flying at 20 km altitude over a thunderstorm in Colorado, USA. The flux of the first glow rapidly intensified and then abruptly decreased within a few tens of milliseconds. On a timescale of seconds, the flux decrease occurred simultaneously with a hybrid intra‐cloud/cloud‐to‐ground lightning discharge beneath the aircraft. However, a more detailed analysis of the discharge dynamics indicated that the discharge activity was unusually calm during the actual period of the flux decrease. The lightning was observed with on‐board antennas, optical sensor, and ground‐based lightning mapping and location networks. Its closest activity was 12 km away from the aircraft, below and slightly ahead the course. The gamma‐ray flux reduction happened roughly in the middle of the lightning development process. The glow spectral analysis for the periods of a weak and strong flux enhancement has been done. The spectra were found to be background‐like and similar to each other. Key Points: A rapid reduction of a gamma‐ray glow flux was observed from an aircraft at 20 km altitude The reduction happened synchronously with a lightning discharge beneath the aircraft and lasted for a few tens of milliseconds Spectral analysis of the weak and the strong glow fluxes do not suggest their different production mechanism